Mind and cosmos. Conception of consciousness in Vasubandhu y Buddhagosha - Arnau Navarro, Juan (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
For the Buddhist scholastic traditions, the universe is inseparable from the mental life of the beings that inhabit it, therefore, the actions of human beings, with their associated mental states, trace the map of the universe and the cosmic calendar. Some researchers have seen in these associations between mind and the universe the «imaginative, mythical and poetic counterpart of meditative states». This article attempts to show how the own scholastic maintains ambiguity on whether the cosmos should be understood as a metaphor of the mind or must be literally identified with her. Some passages establish a complementarity which seems to say the independent existence of both. Be that as it may, contrasting descriptions of mental states with cosmogonists stories allow us a better understand the idea of the cosmos in ancient Buddhism.